2014
DOI: 10.1007/s10967-014-3631-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural environmental radioactivity and the corresponding health risk in Johor Bahru District, Johor, Malaysia

Abstract: This study aims to obtain the baseline data on environmental terrestrial radiation and to assess the corresponding health risk in Johor Bahru District, Johor, Malaysia. The mean activity concentrations of 232 Th, 226 Ra and 40 K were 119 ± 6, 51 ± 4 and 158 ± 21 Bq kg -1 , respectively. Primordial radionuclide 232 Th is the main contributor to gamma dose rate and the mean found to be 135 nGy h -1 . Gross alpha and gross beta activity concentrations in water were 0.012 ± 0.003 and 0.234 ± 0.018 Bq L -1 , respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…The table below shows that the activity concentration of gross alpha and beta are lower than reported studies in Nigeria ( Fasae, 2013 , 2015 ). The tap water results for concentration of gross alpha and beta in this study is higher than similar studies reported in literature ( Damla et al., 2006 ; Darko et al., 2014 ; Saleh et al., 2015 Korkmaz et al., 2016 ). For the ground water: borehole and well water, the activity concentration of gross alpha and beta are higher and lower than reports of Kobya et al.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…The table below shows that the activity concentration of gross alpha and beta are lower than reported studies in Nigeria ( Fasae, 2013 , 2015 ). The tap water results for concentration of gross alpha and beta in this study is higher than similar studies reported in literature ( Damla et al., 2006 ; Darko et al., 2014 ; Saleh et al., 2015 Korkmaz et al., 2016 ). For the ground water: borehole and well water, the activity concentration of gross alpha and beta are higher and lower than reports of Kobya et al.…”
Section: Resultscontrasting
confidence: 80%
“…(2006) 0.006–0.125 0.001–0.667 Tap ans river water Korkmaz et al. (2016) 0.012 0.234 Tap water Saleh et al. (2015) 0.11–16 0.10–16.90 Thermal spring water Sahin et al.…”
Section: Resultsmentioning
confidence: 99%
“…Following the procedure of Fernandez et al [66], according to which more than 50% of the annual effective dose is due to the contribution of the radium, some authors [51][52][53][54] estimate the annual effective dose due to the ingestion of radionuclides through drinking water consumption by using the following formula [67]:…”
Section: The Assessment Of the Annual Effective Dose Using The Gross Alpha Activitymentioning
confidence: 99%
“…Journal of Radioanalytical and Nuclear Chemistry (2021) 327:[49][50][51][52][53][54][55][56][57][58] …”
mentioning
confidence: 99%
“…The radioactivity in soil has been studied in many regions of the world [4][5][6][7][8][9][10][11][12][13]. In India the work on the radioactivity in soil is scattered.…”
Section: Introductionmentioning
confidence: 99%